Contributions of Marxist Thought in the Construction of Critical Political Education Courses - Carnut, Leonardo; Mendes, Áquilas (Critical Education, 2025)
Critical political education courses, as theoretical-philosophical and methodological spatial processes, serve to awaken the working-class consciousness toward a revolutionary praxis. They are regarded as strategic education processes for the organization of the working class for the political struggle toward human emancipation. This study presents a literature review of articles on critical political education courses, obtained from Marxist academic journals. Twenty articles were included in the study, using the following method of selection. The article content was analyzed and discussed along two thematic axes: “Conception of Critical Political Education Courses” and “Contributions of Marxist Critical Theory in the Political Education Courses of Workers.” The study found that the main ideas developed in the articles were “historical-dialectical materialism,” “historical-critical pedagogy,” “socialist pedagogy,” “the pedagogy of social movements,” and “applications to Latin American countries.”